PENGEMBANGAN E-COMMERCE PRODUK UMKM BERBASIS ANDROID DI KOTA SERANG-BANTEN - Arum Wahyuni Purbohastuti; Didik Aribowo (Jurnal Bisnis Terapan, 2019)
Awareness of technology is increasing along with the development of technology from time to time. Sophisticated technology and its use that is easily accessible to every age group. Based on observations and interviews with the community of Micro, Small and Medium Enterprises (MSMEs) in Serang City, Banten Province, a mobile application that is capable of supporting access to information systems for MSMEproducts can be reached more widely. The objectives of this study are: 1) Developing an android-based mobile application system for marketing MSME products at the Department of Industry and Trade and MSME Serang. 2) Knowing the feasibility of an android-based mobile application system for marketing MSME products at the Department of Industry and Trade and MSME Serang City. The research method uses R&D (Research and Development) with a waterfall development model. In this waterfall development model there are four stages, namely requirements analysis, design, implementation, and testing. This research is expected to help the community, especially the SMEs in Serang City, Banten Province to be able to expand and facilitate the marketing of superior products.